Acute kidney injury in imported Plasmodium falciparum malaria. (December 2015) - Koopmans, Liese; Wolfswinkel, Marlies; Hesselink, Dennis; Hoorn, Ewout; Koelewijn, Rob; Hellemond, Jaap; Genderen, Perry
Abstract Background Acute kidney injury (AKI) is a known complication of malaria, and is reported to occur in up to 40 % of adult patients with a severePlasmodium falciparum infection in endemic regions. To gain insight in the incidence and risk factors of AKI in importedP. falciparum malaria, a retrospective analysis was performed on a large cohort of mostly non-immune patients with importedP. falciparum malaria. Aiming to include not only severe but also milder forms of renal failure, the KDIGO criteria were used to define AKI. Methods Clinical and laboratory data from 485 consecutive cases of importedP. falciparum malaria were extracted from the Rotterdam Malaria Cohort database. Acute kidney injury (AKI) was defined using the KDIGO criteria. Univariate and multivariate logistic regression analyses were used to identify risk factors for AKI. Results AKI was seen in 39 (8 %) of all patients and in 23 (38 %) of the 61 patients with severe malaria. Eight patients eventually needed renal replacement therapy (RRT); seven of them already had AKI at presentation. Higher age, higher leucocyte count and thrombocytopaenia were independently-associated with AKI but their positive predictive values were relatively poor. Conclusion AKI was found to be a common complication in adults with importedP. falciparum necessitating RRT in only a small minority of patients. The use of the KDIGO staging allows early recognition of a decline in renal function.